2020
DOI: 10.3389/fenrg.2020.00186
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Pump Shaft Stability Analysis of Multistage Centrifugal Pump During Closed-Valve Start-Up Process

Abstract: In order to analyze the pump shaft stability of multistage centrifugal pump during the closed-valve start-up process, the transient internal fluid field and structural field during the closed-valve start-up process of the TDM 35-140 × 13 segmental multistage centrifugal pump are solved by transient fluid-solid coupling. The transient deformation and vibration velocity of the pump shaft are analyzed. It is found that the maximum deformation amount of the third stage impeller and the pump shaft cylindrical conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Many experts and scholars have carried out research on the transition process of hydraulic machinery and its systems, and the research on the transition process of hydropower stations or pump stations is more mature [7,8]. Its theoretical basis is mainly rigid water hammer theory and elastic water hammer theory, and the analysis method is mainly the characteristic line method in computational fluid dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Many experts and scholars have carried out research on the transition process of hydraulic machinery and its systems, and the research on the transition process of hydropower stations or pump stations is more mature [7,8]. Its theoretical basis is mainly rigid water hammer theory and elastic water hammer theory, and the analysis method is mainly the characteristic line method in computational fluid dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, some studies on the performance of these hydraulic machines under the start-up transition [30][31][32] (SUT) have also been proposed. Long et al [33] researched the SUT of the centrifugal pump using numerical simulation. It was found that in the initial stage of starting, the stall flow rate in the impeller runner is larger, intensifying the rotational stall in the impeller and making the flow more chaotic.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic pulses have a strong impact on the internal flow loss as well as operational stability. Many studies focused on the dynamic pulses in pumps (Long et al, 2020;Peng et al, 20212021;Ye et al, 2021;Zhang et al, 2021). Barrio et al (2008) studied the dynamic pulse mechanism by varying the radial gap of the tongue.…”
Section: Introductionmentioning
confidence: 99%